Analysis of The Influence of Population Number and Regional Minimum Wage on Unemployment in Central Kalimantan - Rima Harati; Heike Delfmann (PT Agung Media Publisher, 2024)
This study aims to examine the impact of population and regional minimum wages on unemployment in Central Kalimantan. Understanding the factors influencing unemployment is crucial for policymakers, particularly in regions with unique economic and demographic challenges like Central Kalimantan. The research uses data from the period 2011-2023, applying Multiple Linear Regression Analysis to investigate the relationship between population (X1), regional minimum wages (X2), and unemployment (Y). Classical assumption tests, including normality, multicollinearity, autocorrelation, and heteroscedasticity, were conducted to ensure the validity of the regression model. The findings indicate that neither population nor regional minimum wages significantly affect unemployment in Central Kalimantan. These results suggest that other factors may play a more significant role in determining unemployment in the region, providing a basis for future research to explore additional variables and more complex interactions affecting regional unemployment rates.